CHANGES IN THE TEMPERATURE FIELD IN REINFORCED CONCRETE STRUCTURES FROM CLIMATIC FACTORS - Zulfiya Shukhratovna Khodjaeva, (International Journal of Innovations in Engineering Research and Technology, 2021)
The introduction of new methods for calculating the temperature field of reinforced concrete structures under the influence of a dry-hot climate, as well as the objective consideration of these methods in the calculation and design of the structure are considered.